1999
DOI: 10.1007/pl00014342
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of prothrombotic risk factors in pediatric patients with malignancy – impact of central venous lines

Abstract: The present study demonstrates the clinical importance of CVL in combination with inherited thrombophilia in the development of thrombosis in pediatric-oncologic patients. Before or shortly after insertion of CVL, patients should be tested for the presence of factor V G1691A mutation, prothrombin G20210A variant and increased lipoprotein (a) values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
3
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 4 publications
0
51
3
2
Order By: Relevance
“…Another study found that 32% of patients who had CVC thromboses had diagnoses of a hypercoagulable state; most had elevated anticardiolipin antibody levels, but there was no greater incidence of prothrombin 20210A mutation, Factor V Leiden, protein C deficiency, or protein S deficiency [62]. In a study in children, however, 63% of those with CVC thromboses did have an inherited risk factor, most of whom were compound heterozygotes [36]. In a related study, this higher risk for CVC thrombosis appeared to occur only in children with acute lymphoblastic leukemia [38].…”
Section: Patientmentioning
confidence: 96%
See 1 more Smart Citation
“…Another study found that 32% of patients who had CVC thromboses had diagnoses of a hypercoagulable state; most had elevated anticardiolipin antibody levels, but there was no greater incidence of prothrombin 20210A mutation, Factor V Leiden, protein C deficiency, or protein S deficiency [62]. In a study in children, however, 63% of those with CVC thromboses did have an inherited risk factor, most of whom were compound heterozygotes [36]. In a related study, this higher risk for CVC thrombosis appeared to occur only in children with acute lymphoblastic leukemia [38].…”
Section: Patientmentioning
confidence: 96%
“…In those that are symptomatic, symptoms include arm/neck/head swelling or pain, headache, numbness of the extremity, erythema of the extremity, phlegmasia, venous distention, and jaw pain. Table 3 lists the studies in which patients with CVCs developed symptoms and then had clots in the affected blood vessel documented by venogram or ultrasound [22,25,[27][28][29][30][31][32][33][34][35][36][37][38][39]. On average, 12% of all patients with CVCs developed symptomatic thrombi but there was a wide range, from 5%-41% of all CVC insertions.…”
Section: Cvc-related Blood Vessel Thrombosis (Dvt)mentioning
confidence: 99%
“…15,21 -23 In addition, there are numerous reports of PT G20210A in combination with another risk factor contributing to thrombophilia. 22,24 Treatment of intracardiac thrombi has included surgical intervention, antiplatelet agents, thrombolytics and anticoagulants. In the neonatal period, surgery and thrombolytics are generally reserved for life-threatening thrombi.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты различных исследований показывают, что наиболее часто ВТ встре-чаются у детей с лимфомами (21,05 %), саркомами (15,62 %) и опухолью Вильмса (42,50 %). При остром лимфобластном лейкозе ВТ выявляются в 10,89 % слу-чаев [3][4][5][6].…”
Section: обзор литературыunclassified